2019
DOI: 10.1088/1367-2630/ab0aa6
|View full text |Cite
|
Sign up to set email alerts
|

Memory-induced complex contagion in epidemic spreading

Abstract: Albeit epidemic models have evolved into powerful predictive tools for the spread of diseases and opinions, most assume memoryless agents and independent transmission channels. We develop an infection mechanism that is endowed with memory of past exposures and simultaneously incorporates the joint effect of multiple infectious sources. Analytic equations and simulations of the susceptible-infected-susceptible model in unstructured substrates reveal the emergence of an additional phase that separates the usual … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…That result is partly verified in Ref. [14] by an independent simulation, based on Ref. [15] and revisited here in Sec.…”
Section: Introductionsupporting
confidence: 74%
“…That result is partly verified in Ref. [14] by an independent simulation, based on Ref. [15] and revisited here in Sec.…”
Section: Introductionsupporting
confidence: 74%
“…When α > α c the steady-state density of the infected nodes exhibits explosive growth with respect to the basic transmission rate and a hysteresis loop emerges. Hoffmann and Boguñá [211] proposed a synergistic cumulative contagion model, which takes into account the memory of past exposures and incorporates the synergy effects of multiple infectious sources. They found that the interplay of the non-Markovian feature and a complex contagion produces rich phenomena, including the loss of universality, collective memory loss, bistable regions, hysteresis loops, and excitable phases.…”
Section: Generalized Social Contagionsmentioning
confidence: 99%
“…Interestingly, non-Markovian effects in recovery processes can also make the network more resilient against large-scale failures [28] and, in some cases, it has been demonstrated that non-Markovian dynamics can be reduced to Markovian dynamics, simplifying the modeling process [24,26,29]. Finally, non-Markovian dynamics may induce an effective complex contagion mechanism, with correlated infectious channels, leading to the appearance of novel exotic epidemic phases [30].…”
Section: Introductionmentioning
confidence: 99%